Authoritites track down police killer - Pappas, Mike (Raton, NM Raton Range, 1989)
Columns written by Mike Pappas, owner of the Sweet Shop Restaurant, for the Raton Daily Range on a wide variety of topics, some historical, some current, some personal.
Newspaper Article by Mike Pappas
Master list item #: 69
File location is in the Raton File Cabinet
Keywords: Davis, Oscar; Norman, Clyde; Brigance, Oscar; Durgeloh (Officer); Johnson, J.W.; Farmer, Tom; O'Neill, Ed; Atkinson (Mr.); Linwood (Sheriff); Stringfellow, Ray; Brigance, Newton; Newby, O.C.; Raton Reporter; Raton Range; Stillwater Jail; Local History; Life and Customs; Raton, New Mexico; Stillwater; Texas; Oklahoma